(untitled) (Revista Angelus Novus, 2014)
The discovery of America presented a set of problems for classification of nature and its peoples. Therefore, the assimilation of this new mainland by European travelers and chroniclers required the development of intellectual tools that profoundly shape the production of cultural meanings in relationship opened. The focus of this article delves into the making of these tools through the appropriation of cultural and symbolic goods made in the descriptions of the New World. Therefore, our interest lies in the perception of this movement from the existing connection between the staple foods like bread and wine and the religious sphere.